ANALISIS STRATEGI PEMASARAN MARKETING MIX DENGAN ANALISIS SWOT UNTUK MENCIPTAKAN KEPUASAN KONSUMEN PADA RAJA CUKUR KEL. CIPONDOH KOTA TANGERANG - Ardi Dandiharja; Reza Khairul Hadi (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
. This research is motivated by the fluctuation in consumer visits and the decline in turnover at Raja Cukur Cipondoh due to suboptimal marketing strategies amidst the barbershop industry competition. This study aims to formulate marketing strategies to create consumer satisfaction using the Marketing Mix 7P framework and SWOT analysis. The research method applied is descriptive qualitative. Data collection was conducted through participatory observation, documentation, and semi-structured interviews with the owner and consumers, which were then validated using source triangulation. The calculation results of the IFAS and EFAS matrices indicate that the company has a strong internal position (strength score 2.1 > weakness 1.2) and significant external potential (opportunity score 2.1 > threat 1.5). Based on the SWOT diagram, the business is in Quadrant I, supporting an aggressive strategy. Research findings reveal that competitive pricing and friendly service are the main strengths, while minimal digital promotion and simple physical appearance are identified as weaknesses. It is concluded that the appropriate strategy is to leverage internal strengths to capture opportunities through optimizing social media promotion and improving physical facilities to ensure sustainable consumer satisfaction.